2016
DOI: 10.1515/hukin-2015-0145
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dehydration Before Training Sessions, Friendly and Official Matches in Elite Female Soccer Players

Abstract: This study aimed to evaluate and compare the hydration states prior to different sporting events (training sessions, friendly and official matches) in elite female soccer players and relate that to the importance that the player attached to the hydration state as a determinant of sports performance. The hydration state of 17 female elite soccer players (age: 21.5 ± 3 years; body mass: 62 ± 6 kg; body height: 165 ± 9 cm) was determined by measuring their urine specific gravity (USG) prior to three different spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 15 publications
7
31
1
2
Order By: Relevance
“…This research showed that the incidence of pre-practice dehydration among junior sub-elite athletes in Yogyakarta is high (90.9%), indicating that athletes and their parents do not understand about the seriousness of fulfilling fluid requirement level in their body prior to training. The research result is similar to a research conducted by Spulveda et al which showed that many young athletes started their training in dehydrated conditions [4,5].…”
Section: Discussionsupporting
confidence: 90%
“…This research showed that the incidence of pre-practice dehydration among junior sub-elite athletes in Yogyakarta is high (90.9%), indicating that athletes and their parents do not understand about the seriousness of fulfilling fluid requirement level in their body prior to training. The research result is similar to a research conducted by Spulveda et al which showed that many young athletes started their training in dehydrated conditions [4,5].…”
Section: Discussionsupporting
confidence: 90%
“…These findings reinforce the importance of stimulating the water intake at all times of the day for soccer players, once you start practicing sports in dehydration conditions cause changes in the physiological homeostasis, including reduction of blood volume, increased heart rate, increased blood osmolarity, decreased blood flow to the skin, decreased sweating rate and heat loss, increased body temperature and increased perceived exertion 26 . Recognizing the importance of hydration for this population, the consumption from 600 to 1,000 ml of a 6 to 10% carbohydrate solution would be most appropriate in this situation 27,28 .…”
Section: Discussionsupporting
confidence: 65%
“…Similar results regarding hydration status on athletes have been reported elsewhere. In a study performed by Castro-Sepúlveda et al (2015) professional soccer players began training sessions with an average USG of 1.026 ± 0.005 (98% dehydration prevalence) [14]. Furthermore, Díaz-Castro et al (2018) observed basketball players with an average USG of 1.021 ± 0.006 (98% dehydration prevalence) [15].…”
Section: Discussionmentioning
confidence: 99%